Improving spectral efficiency in cooperative cellular networks via convex optimisation. (1st January 2013) - Karia, Deepak C.; Lande, B.K.; Daruwala, R.D.
A single base station communicating with multiple users over orthogonal channels being assisted by multiple relays is considered in this paper. Recent works have suggested that a single relaying environment is the best relaying choice in such a scenario. However, in a multiuser setting, optimal relay assignment is a combinatorial problem. Previous work, largely deals with mesh networks, addressing the problem of selection of relay, assigned to the various users using the concept of beaconing, followed by power allocation through convex optimisation. However, this increases system overhead, thereby reducing the user throughput. In this paper, we propose a unified system model, using realistic channels that not only demonstrates the efficacy of the idea proposed, but also resolves the problem of low spectral efficiency. The proposed idea uses a beacon signal only for deciding whether to use a relay or not, thereby leaving the decision of power allocation and relay assignment to the users in need, via convex optimisation.